Rediseño de una herramienta informática para controlar los costos de los sistemas QHSE de acuerdo a la última actualización de las normas ISO 9001, 14001 y OHSAS 18001 en pequeñas medianas empresas en Bogotá D.C. (2017)
The purpose of this degree work was to redesign an IT tool to control the costs of QHSE management systems according to the latest update of the ISO 9001, 14001 and OHSAS 18001 standards in small and medium-sized enterprises in Bogotá DC. To fulfill this objective, a survey was designed to evaluate the current situation of SMEs in terms of cost controls in management systems, the subjects of the sample were 50 natural persons belonging to SMEs and knowledgeable about the management of Management in their organizations, the total number of people surveyed were 60 and there was a need to discard 10 people since the companies for which they work are multinational or large and these are not part of this work. In the tabulation of the information the importance of the generation of the tool was identified since in the majority SMEs do not have systems that allow them to quantify and control their costs, from this they were evaluated different computer tools deciding the one of greater knowledge And ease of access for any natural or legal person, Excel, under which all necessary standards were parameterized with the objective of quantifying the associated costs for each management system, reflecting indicators of management and budget behaviors vs. reality in organizations by Periods of time. The application of this tool can be given to SMEs with all the management systems implemented or with any of them, ie it is not restrictive or conditional to be certified in all. The version presented, is of academic type, but it is applicable to any SME in Colombia.